ANALISIS VARIASI BIAYA KONSTRUKSI ATAS DASAR PERBEDAAN KONSTRUKSI PONDASI DAN LANTAI - Muhammad Muhammad (Lambung Mangkurat University Press, 2019)
There are various types of shophouses construction in the city of Banjarmasin. Some use a foundation centered on the column, and there is also a continuous foundation on sloof. There is a floor construction that uses a staging system, and some uses a backfill system, so the cost per square meter of shop-building costs also varies. The research objective is to find out / find variations in construction costs per-m2 based on the type of foundation and floor construction and what is the minimum construction cost per-m2 in the construction of shophouses in the city of Banjarmasin if related to the types of foundation and floor construction. This research seeks to explore and utilize data obtained from the construction of shophouses built around the Banjarmasin city area, both those that have already been completed and those that are still in the construction stage. This study includes a calculation of the cost of building a shop construction on 4 types of combined construction, namely 2 types of foundation construction and 2 types of floor construction so that it can be seen the minimum cost of a combination of the two types of shophouse construction in the city of Banjarmasin.